Achieving climate smart cocoa at scale in Central America and the Caribbean - Bunn, Christian (International Center for Tropical Agriculture, 2019)
This document summarizes two documents with results of a climate analysis made to support efficient adaptation at scale. We developed an Atlas of Climate Change Impacts on cocoa production in Central America and the Caribbean, which contains maps of agro-climatic zones and gradient impact maps for cocoa, and a list of climate smart practices that have the potential to confront projected climatic change and improve the resilience at farm level. Because many solutions have a long lead time, the challenge is to use currently available means and prioritize them to take into account evolving climate change. The set of practices was developed through a series of participatory workshops in Honduras, Nicaragua, Guatemala, Dominican Republic, and El Salvador and validated through a review of scientific literature.